Justice as Fairness in South Africa? Rawls and the Failure of the Broad-based Black Economic Empowerment (BBBEE) Act of 2003 - Stodel, Shannon (The Stellenbosch Socratic Journal, 2022)
John Rawls’s moral theory aims to achieve a form of distributive justice that is founded upon fairness. In this paper, the criteria and principles, as presented by Rawls in his theory of justice as fairness, are applied to the enactment of the Broad-Based Black Economic Empowerment Act (BBBEE) in an effort to evaluate whether it satisfies his stipulated conditions. The Broad-Based Black Economic Empowerment Act of 2003 was introduced in South Africa as a means to further mitigate the structural patterns of disadvantage that disproportionally affect the black majority of the population in the wake of Apartheid. Justice as fairness is initially theoretically conceptualised and contextualised through an explanation of its main elements and thought experiments; namely, those of the basic structure of society, the Original Position and the Veil of Ignorance, as well as the principles of justice. In this paper, the practical application of this theory of distributive justice is facilitated through the use of the BBBEE Act in an effort to establish whether the act achieves the kind of justice as fairness that Rawls envisions. This analysis is facilitated through a qualitative comparison of the successes and alignments, as well as the failures and divergences of the policy to the theory itself. The outcome of the analysis suggests that the BBBEE policy satisfies some of the Rawlsian criteria for justice as fairness initially, but ultimately fails in practice.